GLOBALIZATION OF TRANSPORT LINKS AS A FACTOR IN MODERNIZATION AND DEVELOPMENT OF RIVER PORTS OF RUSSIA AND THEIR INTEGRATION INTO THE SYSTEM OF TRANSPORT COMMUNICATIONS - S. Znatnov (Вестник университета, 2019)
The article is devoted to the integration of Russian river ports in the system of international transport corridors. The author gives a brief comprehensive assessment of current status of river ports. Considerable attention is paid to the problems of functioning of the port sector. Analyses the future actions for the development of inland waterways. Identifies and describes the generic problems impeding the integration of ports in the system of transport corridors.